Medication adherence and its associated factors among type 2 diabetic patients in Ethiopian General Hospital, 2019: Institutional based cross-sectional study - Belete Achamyelew Ayele; Sofonyas Abebaw Tiruneh; Asnakew Achaw Ayele; Melaku Tadege Engidaw; Getachew Yideg Yitbarek; Alemayehu Digssie Gebremariam (Public Library of Science (PLoS), 2022)
Introduction Globally, diabetes mellitus is becoming a major public health problem in developing countries. Diabetic medication has a major role in glycemic control. However, poor adherence to diabetes medication leads to increased morbidity and morbidity. This study aimed to determine diabetes medication adherence and its associated factors among type two diabetes (T2DM) patients from December 01, 2019 to December 31, 2019, at Debre Tabor General Hospital, Northwest Ethiopia. Methods An institutional-based cross-sectional survey was conducted with a sample of 422 T2DM at Debre Tabor General Hospital diabetic clinic, Ethiopia. The study was conducted from December 01-31/2019. Medication adherence was measured using the 8-item Morisky Medication Adherence Scale. The data were analyzed using STATA version 15.1 software. Logistic regressions were carried out to identify independent predictors for T2DM adherence. P-value less than 0.05 was used to declare statistical significance. Results A total of 408 T2DM patients were recruited for this study with a response rate of 96.7%. Overall, 58.33% (95% Confidence Interval (CI): 53.47-63.03) T2DM patients had good medication adherence.T2DM patients who were taking both oral and injectable anti-diabetic medications (Adjusted odds ratio (AOR) = 1.98, 95% CI: 1.16-3.39), got the prescribed anti-diabetic medication from the hospital (AOR = 0.51, 95% CI: 0.32-0.80), having own glucometer at home (AOR = 0.30, 95% CI: 0.16-0.54), and having good diabetes-related knowledge (AOR = 0.50, 95% CI: 0.27-0.90) were a significant determinant factors for anti-diabetic medication adherence. Conclusion Overall, more than half of T2DM patients had good medication adherence. Medication type, access to anti-diabetic medication, having own glucometer at home, diabetes-related knowledge were independent predictors of medication adherence. T2DM patients should have own glucometer at home and health promotion should provide about diabetic Mellitus for T2DM patients.